Time-Dependent Thermal Convective Circulation of Hybrid Nanoliquid Past an Oscillating Porous Plate with Heat Generation and Thermal Radiation - Mallesh, M. P.; Makinde, O.D.; Rajesh, V.; Kavitha, M. (Journal of Applied Nonlinear Dynamics, 2026)
The present study explores the impact of heat generation and thermal radiation on the time-dependent free convective flow of a hybrid nanofluid past a vertically oscillating porous plate.The nonlinear partial differential equations, which control the transport phenomena, are transmuted into dimensionless form with appropriate parameters. The resulting equations with appropriate boundary conditions are solved numerically with the aid of the Galerkin finite element method. The impact of sundry parameters such as Thermal Grashof number (Gr), Radiation Parameter $(N)$, Heat generation Parameter $(Q)$, Time ($t$), Nanoparticle Volume fraction of $Al_{2}O_{3}$ ($δ _{2} $), Suction Parameter ($λ $), Nusselt number ($Nu$), Skin friction coefficient ($C_{f} $) that controls the flow velocity and temperature distributions are evaluated extensively with the aid of graphs and tables. Moreover, a comparison between the regular Silicon dioxide water $(SiO_{2} -H_{2} O)$ nanoliquid and Silicon dioxide/Aluminum oxide water $(SiO_{2} -Al_{2} O_{3} -H_{2} O)$ hybrid nanoliquid is provided in skin friction and heat transfer enhancement. The present numerical solution is in good agreement with the analytical solution for the special cases of the problem. The current investigation is of immense apropos in the cooling of nuclear reactors, microelectronics, electromechanical systems, and drug delivery in chemotherapy.